Germany : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation highlights that economic activity in Germany is slowly picking up, and there is scope for some further firming of growth in the course of 2006. The recovery, however, remains unbalanced, and strong exports have yet to feed through into higher household spending. Although the risks to the outlook are broadly neutral, an unwinding of global imbalances and higher oil prices could yet provide headwinds for the recovery. On balance, headline growth is forecast at 1 percent in 2005 and 1.5 percent in 2006, implying a gradual recovery in working-day-adjusted terms.